Humanitarian intervention and responsibility to protect: the fragile legal regulation of a moral imperative - García Ruiz, Carmen Rocío (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2022)
The concepts of humanitarian intervention and responsibility to protect have been formulated aiming to provide an adequate response to an old question: how to respond to violations of rights committed by states on their own subjects. Based on the formulation of the just war or the very conception of humanity, it underlies the difficult relationship between three of the structural principles of Public International Law: sovereignty, use of force and protection of human rights. This article analyzes the evolution of both concepts, the differences between them and the obstacles that hinder their effective application.
Keywords: humanitarian intervention; responsibility to protect; human rights